Um estudo sobre o clima organizacional nos departamentos de contabilidade de empresas de grande porte - Silva, Maria Luzia Rosângela da (2010)
In view of the fact that Accounting does not just consist of techniques and that the behavioral aspects of the accounting professionals do influence its efficiency, the diagnosis and the follow-up of the organizational environment is an instrument for the accountant-organization relationship to result in higher levels of motivation. This dissertation aims at getting to know the accountants perception of the organizational environment and the aspects that can be influential on their motivation. For that purpose, the literature research process comprised reviewing national and international data banks for thesis, dissertations, articles, and books in the fields of accounting, business administration, sociology and psychology. The field research used a self-administered survey, with 28 questions based on the Kolb Scale (1978), which consists of conformity, support and human warmth, leadership, rewards, patterns, transparency, and accountability elements. The sample included 50 accountant respondents across the accounting departments from 50 large-sized companies in the State of São Paulo. The information was dealt with statistically for the hypotheses tested on field of activity, level of schooling, gender, experience and position, which provided the results for the analysis of the 7 Kolb Scale (1978) factors, associated with the needs for achievement, power, and affiliation under the McClelland Theory (1972). It was concluded that gender exerts influence on the perception of the environment, particularly regarding the conformity, leadership and accountability factors; the male accountant perceives all of the environmental factors better, with the exception of conformity, which is better portrayed by women. There is a difference in the perception of the environment for schooling level, especially for the conformity, leadership, patterns, rewards, transparency, and accountability factors. The accountants holding graduate degrees show a better perception of the environmental factors. Experience influences the perception of the environment more significantly for the conformity, leadership, reward, and accountability factors. The experience range that most favorably portrays the environment is from 15 to 25 years old. There is a difference in perception of the environment for job position, mainly regarding the support, conformity, leadership, reward, and accountability factors. The highest positions better portray the leadership, accountability, reward, and patterns factors. The research inferred that the leadership factor is the most desired by the accountants, while conformity is the factor with greatest acceptance. Based on these results, it is recommended that new behavioral research be conducted for the analysis of the social-technical needs of Accounting